2008
DOI: 10.3354/meps07333
|View full text |Cite
|
Sign up to set email alerts
|

Effects of phytoplankton physiology on export flux

Abstract: Estimates of phytoplankton sticking efficiency (α) were made in the laboratory within a 1500 l annular flume mesocosm over the initiation, maintenance and senescence phases of a bloom of the diatom Thalassiosira pseudonana. The spatially weighted mean turbulence kinetic energy dissipation rate in the annular flume was comparable to values found at the ocean's surface on a calm day. The α of T. pseudonana varied as a result of physiological state, and ranged from 0 ± 0.08 during the bloom initiation to 0.26 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 71 publications
2
41
0
Order By: Relevance
“…Several studies have shown that the balance between TEP and solid particles, such as cells, co-determines the efficiency of particle coagulation and formation of macroscopic aggregates (Logan et al, 1995;Engel, 2000;Kahl et al, 2008). Particle aggregates are a major vehicle for organic matter export to the deep ocean.…”
Section: Tep Production and Carbon Cyclingmentioning
confidence: 99%
“…Several studies have shown that the balance between TEP and solid particles, such as cells, co-determines the efficiency of particle coagulation and formation of macroscopic aggregates (Logan et al, 1995;Engel, 2000;Kahl et al, 2008). Particle aggregates are a major vehicle for organic matter export to the deep ocean.…”
Section: Tep Production and Carbon Cyclingmentioning
confidence: 99%
“…Thus, the mechanisms behind diatom dominance in lentic and lotic water might not be identical because hydrodynamic conditions may differ between these types of systems. Thus, the flow regime should be considered as a prerequisite inducement for diatom blooms in natural water bodies [13,28].…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…Release of exudates by diatoms is species-specific and depends on environmental conditions (Myklestad, 1995;Kahl et al, 2008). In laboratory experiments, three different types of aggregation behavior were distinguishable: (i) non-aggregating species that produce very little TEP (for example, Thalassiosira weissflogii), (ii) aggregating species that generate a cell coating of sticky TEP-like material but produce no free TEP (for example, Nitschia angularis) and (iii) species that generate copious amounts of TEP and form TEP-rich aggregates (for example, Chaetoceros sp.)…”
Section: Introductionmentioning
confidence: 99%